If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(w + 2) + -1w + -7 = -6(w + 4) + 7 Reorder the terms: -5(2 + w) + -1w + -7 = -6(w + 4) + 7 (2 * -5 + w * -5) + -1w + -7 = -6(w + 4) + 7 (-10 + -5w) + -1w + -7 = -6(w + 4) + 7 Reorder the terms: -10 + -7 + -5w + -1w = -6(w + 4) + 7 Combine like terms: -10 + -7 = -17 -17 + -5w + -1w = -6(w + 4) + 7 Combine like terms: -5w + -1w = -6w -17 + -6w = -6(w + 4) + 7 Reorder the terms: -17 + -6w = -6(4 + w) + 7 -17 + -6w = (4 * -6 + w * -6) + 7 -17 + -6w = (-24 + -6w) + 7 Reorder the terms: -17 + -6w = -24 + 7 + -6w Combine like terms: -24 + 7 = -17 -17 + -6w = -17 + -6w Add '17' to each side of the equation. -17 + 17 + -6w = -17 + 17 + -6w Combine like terms: -17 + 17 = 0 0 + -6w = -17 + 17 + -6w -6w = -17 + 17 + -6w Combine like terms: -17 + 17 = 0 -6w = 0 + -6w -6w = -6w Add '6w' to each side of the equation. -6w + 6w = -6w + 6w Combine like terms: -6w + 6w = 0 0 = -6w + 6w Combine like terms: -6w + 6w = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 3x-1=4x+1 | | -29p-6(5-6p)=3(p-4)-34 | | .5x(x)-242=0 | | 5z^2-7z=-3z-7 | | 4.9t^2+15t+1.9=0 | | (x+1.8)-(0.1x+7)=9 | | 1-5x-y=0fory | | -3(2-4n)=10 | | 0.34=logx | | (x+26)-(0.1x+8)=10 | | 7(5(x-1))+3=17 | | (x+2.7)-(0.7x+4)=12 | | -4x+6x-7=2(x-3)-4 | | 5+10x=4+10x | | 9x-5=2(4x+3)-1 | | -6(y+9)=-5y-5 | | 15z^4-13z^2+2=0 | | -7(z-3)=-6z-9 | | x-44=9 | | 9(x+4)-3x=3(2x+2)-7 | | 45=14+16 | | x^2-12+9=0 | | ab=a-b | | -2(t-4)+7t=8t-6 | | 21x+7-23x=6-9 | | (8a+2b)+(2c-8a)= | | 4+5n=7n+4 | | 47y=23(2y+16) | | 5x^3+16x^2+8x+16=0 | | 7x+15y=192 | | 2X^2-5=123 | | x^4+38x^3+10=36 |